Digitization as an opportunity to preserve endangered fonds - case in the State Agency of Kosovo Archives - Bekim, Aliu (Moderna arhivistika, 2019)
The article discussesissues of preservation and access to the "District Court in Prizren" fonds and the use of digitization to capture the content of endangered documents. Digitization of the "District Court of Prizren" fonds enables capturing and preserving the content of documents, which cannot be recovered or restored. This paper contributes to the discussion by exploring access to and preservation of endangered archival fonds and collections and presents the digitization project of the "District Court in Prizren" fonds at the State Agency of Kosovo Archives as a case study.
Keywords: access; digitalizacija; digitization; dostop; izvirni dokumenti; original documents; preservation; restavracija in konzervacija; restoration and conservation; risk of destruction; tveganje; varstvo